Inventory management - V. I. Pochabov; A. N. Korbut; V. E. Klichevskaya (Наука и техника)
The paper reveals the methodology for justification of rational inventory scope. The concrete example of its calculation is given in the paper. The diagram of the inventory changes has been plotted which makes it possible to manage it efficiently.